Window in Iran Islamic Architecture with Emphasis on Role of Light - Kateb, Fatemeh (Journal of History Culture and Art Research, 2018)
Presence of light during history and in various architectural oeuvres, in addition to functional aspect, as factor for illumination and life conferring to daily activities, it has been abundantly addressed from spiritual aspect and in doctrinal discussions of religions. During Islamic epoch, light was manifestation of god existence and for this reason, it is respected and deemed as sacred. Islamic architecture particularly in Iran has a special emphasis on the light. This study is carried out by descriptive analytical method. Results showed that window as the inlet of light preserves light presence hierarchy, also in symbolic and mystical concepts like excellence, upward tendency and establishing a spiritual space in architecture, each one has been manifested in some way or another.